Enhancing Soil Carbon Sequestration and Land Restoration through Tropical Forest Management - Rahman, Md. Shoaibur; Raihan, Asif; Islam, Samanta; Paul, Pramila; Karmakar, Sourav (Journal of Agriculture Sustainability and Environment, 2023)
Soil has a high capacity for absorbing carbon dioxide (CO2). The significance of soil organic carbon (SOC) in tropical regions is often overlooked, despite its crucial role. This study investigates the potential of forest management to enhance the sequestration of SOC and rehabilitate degraded tropical ecosystems. Sequestering soil organic carbon has the potential to improve soil fertility while also mitigating land degradation and reducing greenhouse gas (GHG) emissions. The improvement of soil structure, aggregation, infiltration, faunal mobility, and nutrient cycling (specifically carbon, nitrogen, phosphorus, and sulfur) is observed. Managing forest ecosystems enhances carbon sequestration, mitigates climate change, and rehabilitates degraded land. By integrating organic residue management with nitrogen-fixing plants, afforestation or reforestation of marginal or degraded lands can effectively increase carbon storage in both biomass and soil. This approach also promotes soil health, improves food productivity, restores land quality, and contributes to the reduction of GHG emissions. The sequestration of carbon promotes the biological, physical, and chemical fertility of the soil, hence enhancing soil health.